2004
DOI: 10.1038/nature02363
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-mediated repression of rolled leaf1 specifies maize leaf polarity

Abstract: In both animals and plants, many developmentally important regulatory genes have complementary microRNAs (miRNAs), which suggests that these miRNAs constitute a class of developmental signalling molecules. Leaves of higher plants exhibit a varying degree of asymmetry along the adaxial/abaxial (upper/lower) axis. This asymmetry is specified through the polarized expression of class III homeodomain/leucine zipper (HD-ZIPIII) genes. In Arabidopsis, three such genes, PHABULOSA (PHB), PHAVOLUTA (PHV) and REVOLUTA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
570
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 641 publications
(610 citation statements)
references
References 25 publications
27
570
0
8
Order By: Relevance
“…miR-165/166 regulates the expression of prohibitin (PHB) in Arabidopsis and RLD1 in maize. Mutations in the miR-165/166 complementary site in RLD1 causes an accumulation of RLD1-mRNA, suggesting the role of miRNAs in the regulation of genes involved in the development of maize [42]. In Arabidopsis, APETALA2 (AP2) regulates the developmental timing of flowers.…”
Section: Mirnas In Plantsmentioning
confidence: 99%
“…miR-165/166 regulates the expression of prohibitin (PHB) in Arabidopsis and RLD1 in maize. Mutations in the miR-165/166 complementary site in RLD1 causes an accumulation of RLD1-mRNA, suggesting the role of miRNAs in the regulation of genes involved in the development of maize [42]. In Arabidopsis, APETALA2 (AP2) regulates the developmental timing of flowers.…”
Section: Mirnas In Plantsmentioning
confidence: 99%
“…They are involved in regulating the various aspects of shoot morphogenesis from meristem establishment and maintenance (Juarez et al, 2004, McHale and Koning, 2004, Mallory et al, 2004aJuarez et al, 2004;Zhong and Ye, 2004;Bowman, 2004;Bao et al, 2004;Kim et al, 2005) to leaf development including abaxial-adaxial polarity (Palatnik et al, 2003), organ boundaries (Laufs et al, 2004), shape and complexity (Ori et al, 2007).…”
Section: Functions Of Micro Rnamentioning
confidence: 99%
“…Leaf development is regulated by modulating the expression of class-III homeodomain leucine zipper (HD-ZIP) transcription factor genes, which control leaf patterning along adaxial/abaxial axis (Juarez et al, 2004). PHABULOSA (PHB), PHAVOLUTA (PHV), and REVOLUTA (REV) are three closely related Arabidopsis HD-ZIP transcription factors that are the targets of miR165 and miR166 (Emery et al, 2003;Bao et al, 2004;Bowman, 2004;Juarez et al, 2004;Mallory et al, 2004b;Zhong and Ye, 2004;Kim et al, 2005;Williams et al, 2005b;Ko et al, 2006).…”
Section: Functions Of Micro Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the rolled-leaf mutants in maize shows that the role of HD-ZIPIIIs in adaxial specification is conserved between monocots and eudicots. Juarez et al (2004a) have demonstrated that the maize ortholog of the revoluta gene, Rld1, was misexpression in the semidominant mutant Rld1-Original (Rld1-O), which results from a single nucleotide substitution in the miRNA166 complementary site.…”
Section: Control Of Leaf Development In Ricementioning
confidence: 99%